Building co-curricular learning experiences: Lessons from a student-driven experiential learning initiative underpinned by a student-staff collaborative model - Lam, Man Ho Adrian; Tam, Ching Hin, Anfield (International Journal for Students as Partners, 2022)
In this case study, both authors look into their experiences with a student-driven experiential learning initiative in the form of an academic services committee. The committee embodies a developing community of undergraduate students reading the double degrees in government and laws and also aims at promoting the scholarly study of public affairs and jurisprudence within a traditional and comprehensive research-intensive Hong Kong university. As the flagship student community of the double degree programme, the committee provides tailor-made services for current students and connects them to alumni networks. The authors critically evaluate the multipurpose nature of the committee by applying the five criteria for successful staff-student collaborations, namely (a) reciprocal trust and respect, (b) self-efficacy, (c) flexibility and autonomy, (d) commitment, as well as (e) ownership and responsibility (Martens et al., 2019). Within a synergic collaborative model, students can assume a leadership role in creating and managing multidisciplinary co-curricular learning experiences, with faculty members only assuming indirect, non-voting, and advisory roles under limited circumstances.